EDUARDO PRIETO - Los laberintos del aire - Martínez García-Posada, Ángel (ZARCH, 2024)
EDUARDO PRIETO Los laberintos del aire Ediciones Asimétricas, Madrid, 2023, 223 pp. Tapa blanda. 24 € Idioma: Español ISBN: 978-84-19050-70-0